Chromosome-level subgenome-aware de novo assembly provides insight into Saccharomyces bayanus genome divergence after hybridization - Gardner, Cory; Chen, Junhao; Hadfield, Christina; Lu, Zhaolian; Debruin, David; Zhan, Yu; Donlin, Maureen J.; Ahn, Tae-Hyuk; Lin, Zhenguo (Genome Research, 2024)
Interspecies hybridization is prevalent in various eukaryotic lineages and plays important roles in phenotypic diversification, adaptation, and speciation. To better understand the changes that occurred in the different subgenomes of a hybrid species and how they facilitate adaptation, we have completed chromosome-level de novo assemblies of all chromosomes for a recently formed hybrid yeast, Saccharomyces bayanus strain CBS380, using Oxford Nanopore Technologies' MinION long-read sequencing. We characterize the S. bayanus genome and compare it with its parent species, Saccharomyces uvarum and Saccharomyces eubayanus, and other S. bayanus genomes to better understand genome evolution after a relatively recent hybridization event. We observe multiple recombination events between the subgenomes in each chromosome, followed by loss of heterozygosity (LOH) in nine chromosome pairs. In addition to maintaining nearly all gene content and synteny from its parental genomes, S. bayanus has acquired many genes from other yeast species, primarily through the introgression of Saccharomyces cerevisiae, such as those involved in the maltose metabolism. Finally, the patterns of recombination and LOH suggest an allotetraploid origin of S. bayanus. The gene acquisition and rapid LOH in the hybrid genome probably facilitated its adaptation to maltose brewing environments and mitigated the maladaptive effect of hybridization. This paper describes the first in-depth study using long-read sequencing technology of an S. bayanus hybrid genome, which may serve as an excellent reference for future studies of this important yeast and other yeast strains.